2013
DOI: 10.1111/and.12113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endothelial nitric oxide synthase (eNOS) G894T polymorphism and semen parameters in a Chinese Han population

Abstract: Previous studies have shown that endothelial nitric oxide synthase (eNOS) gene may be involved in abnormal semen parameters. However, the relationship between eNOS G894T polymorphism and semen parameters remains controversial. The purpose of this study was to investigate the association of eNOS G894T polymorphism and semen parameters. The genotype frequency of eNOS G894T was determined in 270 idiopathic asthenozoospermia patients and 248 ethnically matched healthy volunteers using iPLEX genotyping assays on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In an Italian population, the eNOS 894G>T variant was associated with asthenozoospermia and sperm motility [ 48 ]. Similar results were reported in a Chinese cohort [ 49 ]. In Korean infertile men, sperm morphology was associated with the 4a4b eNOS polymorphism, a sequence variant with variable number of tandem 4a4b repeats in intron 4 [ 51 ].…”
Section: Genetic Variations In Antioxidant Genes Associated With Msupporting
confidence: 91%
“…In an Italian population, the eNOS 894G>T variant was associated with asthenozoospermia and sperm motility [ 48 ]. Similar results were reported in a Chinese cohort [ 49 ]. In Korean infertile men, sperm morphology was associated with the 4a4b eNOS polymorphism, a sequence variant with variable number of tandem 4a4b repeats in intron 4 [ 51 ].…”
Section: Genetic Variations In Antioxidant Genes Associated With Msupporting
confidence: 91%
“…A total of 192 idiopathic asthenoteratozoospermic patients with low sperm motility (rapid forward progressive motile sperm, grade A <25 %, and forward progressive motile sperm, grade A+B< 50 %), who had failed to accomplish pregnancy in more than 1 year of unprotected sexual intercourse were enrolled in our study. Exclusion criteria were performed as described previously [11]. Partners of these infertile men enrolled in our study were healthy women who were not suffering from diseases, such as severe reproductive system infection and sexual hormone disturbance [11].…”
Section: Subjects Sample Collection and Testingmentioning
confidence: 99%
“…Exclusion criteria were performed as described previously [11]. Partners of these infertile men enrolled in our study were healthy women who were not suffering from diseases, such as severe reproductive system infection and sexual hormone disturbance [11]. A total of 288 ethnically matched volunteers with normal sperm motility were enrolled and served as controls.…”
Section: Subjects Sample Collection and Testingmentioning
confidence: 99%
“…eNOS gene is mapped to chromosome 7q35-36 and contains 26 exons that span 21 kb 1819. Three important single nucleotide polymorphisms (SNPs) in the eNOS gene (G894T, intron 4, and T-786C) have received substantial attention in the last few years, especially in relation to ED 20212223. A few studies reported positive associations of G894T, T-786C, and intron 4 with the risk of ED 242526.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies reported positive associations of G894T, T-786C, and intron 4 with the risk of ED 242526. However, other studies contend that this association of SNPs of eNOS gene appear to be a “bystander” effect for ED risk 22327. In this context, we used a meta-analysis framework to investigate the associations between G894T, intron 4, T-786C SNPs of eNOS gene, and the risk of ED.…”
Section: Introductionmentioning
confidence: 99%